26‐4: Computer‐Aided Optimization of Multilayer OLED Devices. Issue 1 (30th May 2018) - Symalla, Franz; Friederich, Pascal; Kaiser, Simon; Strunk, Timo; Neumann, Tobias; Wenzel, Wolfgang
Abstract : Development of efficient OLED devices is presently driven by experimental trial&error R&D. We developed a bottom‐up multiscale modeling approach enabling the computation of device properties without the use of experimentally determined parameters. Researchers can identify bottlenecks, develop new materials and optimize devices using computer aided design.